Institutions, resources, and organizational effectiveness in Africa - Zoogah, D.; Peng, Mike; Woldu, H. (2015)
© The Academy of Management Perspectives. While management research has made significant progress in globalizing its reach, African organizations have remained a missing link. We argue that Africa-focused management research may address the major problem of organizational effectiveness through work on the two major theoretical building blocks: institutions and resources. Building a model of organizational effectiveness in Africa, this article discusses the interactive processes within each of the two building blocks and the transformational mechanisms that link each theory and organizational effectiveness in the African context.